Low-achievement factors from language teachers’ perspective: evidence from an EFL context - Heidari, Hadi (2015)
Current study aimed to explore the factors related to the high school students’ low achievement in English course from teachers’ perspectives in Ardebil city, Iran. Cluster random sampling was utilized and the participants of the study were 27 English teachers teaching in high schools of an EFL context during the fall term of 2012. The required data were gathered during the fall term of 2012 through a researcher-made questionnaire. The instrument was first piloted before it was administered and it showed the reliability of 0.81. The findings were analyzed using descriptive statistics and statistical indicators like frequency, percentage, and mean. SPSS software (version 20) was used to run t-tests and ANOVA to analyze the closed items of the questionnaire. The findings revealed that from the teachers’ viewpoints, the teachers-based factors were identified to be the most relevant reasons for high school students’ low achievement in English course.